Effects of Health Promotion Program on Body Mass Index, Weight, Waist Circumference, and Food Consumption Behavior Among Overweight or Obese Nursing Students in Chaiyaphum Rajabhat University Chaiyaphum Province - Robrujen, Suwimolrat; Chaleoykitti, Saisamorn; Thongkwan, Watcharapon; Somhom, Wanpen; Honghian, Hatthaya; Kanman, Parinyaporn; Khala, Jirawan; Sangjun, Chutinan; Laokham, Natthakan; Boonjong, Sawitree (Journal of health and health management, 2025)
This quasi-experimental study aimed to compare the pretest and posttest of average BMI scores weight and waist circumference, and mean food consumption behavior among overweight or obese nursing students in Chaiyaphum Rajabhat University. based on Pender’s health promotion of Pender and Killer of create motivation theory. The samples consisted of 30 people is he 1 2 3th year nursing students who were recruited into an experimental, (BMI ≥23 kg/m2), Female and male students have waist circumferences greater than 80 centimeters and 90 centimeters, respectively. The experimental group received a health promotion program through exercise for 8 weeks with knowledge, and actions to lose weight. The research instruments comprised food consumption behavior and BMI, weight and waist circumference. Passed inspection by 3 experts Content validity Index: CVI and reliability (.91 and .89, respectively). Data were analyzed using descriptive, with the average (M) Standard deviation (SD) and Paired Sample- t-test statistics. The research findings revealed that after a health promotion program through exercise the experimental group had a statistically not significantly different (t = .427NS, .562NS, 0.967NS) not decrease in mean body mass index score, weight, and waist circumference (p<.05) and the food consumption behavior before and after joining the health promotion program was significantly different (p< .05)